Implementasi Project Management Body of Knowledge (PMBOK) pada Pembangunan Fasilitas Sisi Udara Bandar Udara Mentawai Baru di Daerah 3T Kepulauan Mentawai - Rudi Pitoyo; Zaitul Zaitul; Khadavi Khadavi (Universitas Batanghari Jambi, 2026)
In disaster situations, airports serve as vital infrastructure for evacuation and logistics distribution due to their ability to operate quickly, safely, and relatively independently from disruptions to land and sea transportation. Limited sea and air transportation fleets in the Mentawai Islands result in minimal crossing and flight services. To address these limitations, the government developed the New Mentawai Airport as a replacement for Rokot Airport. This condition highlights the importance of evaluating project management implementation to ensure the success of airside facility development in remote and underdeveloped regions. This study aims to identify Project Management Body of Knowledge (PMBOK) factors, determine the level of PMBOK implementation, and analyze the most influential PMBOK factors affecting project success in the construction of airside facilities at New Mentawai Airport. A quantitative research approach was employed by distributing questionnaires to all personnel involved in the project, including the project owner, construction management, and contractors. The collected data were analyzed using validity and reliability tests, descriptive analysis, classical assumption tests, and regression analysis. The results indicate that thirteen PMBOK factors were implemented at a very high level, covering project integration, scope, time, cost, quality, human resources, communication, risk, procurement, occupational health and safety, environmental management, financial management, and claims management. Partially, project risk management and project cost management were identified as the most significant factors influencing project success. It is recommended that risk management and cost control be strengthened from the planning stage through project execution to improve the success of infrastructure development projects in remote areas.